Wayang Kulit Kelantan: The Challenges Between Traditional and Digital Media - Abdul Ghani, Dahlan Bin (Arte, Individuo y Sociedad, 2012)
Traditional Malay theatre arts such as Wayang Kulit Kelantan or Shadow Play puppet Kelantan in Malaysia has been a form of entertainment. Unfortunately, this shadow play puppet has lost it touch and is slowly fading among the society in Malaysia. This paper will focus both on the traditional method and the animation method to create Kelantan shadow play 3D visualization digital puppetry. The paper will begin with some research on previous work related to traditional shadow play puppet and will name some efforts made to digitizing this type of performance. The paper will also look into the results of comparing the two techniques. The final section of the paper will attempt to highlight the challenges and future aspects of animation and traditional shadow play that would be significant in helping bring back the popularity of this Malaysian performing arts masterpiece.